PENGEMBANGAN SEKTOR INDUSTRI MANUFAKTUR YANG BERKELANJUTAN DAN BERWAWASAN LINGKUNGAN DENGAN MENGGUNAKAN PENDEKATAN METODE INPUT OUTPUT DAN INDUSTRIAL POLLUTIONS PROJECTION SYSTEM (IPPS) - Wawan Hermawan (Center for Economic Studies Universitas Katolik Parahyangan, 2003)
Indonesian economic growth is inseparable from the vast growth of manufacturing industry sector, which contribute dominantly to the GDP. The increasing pollution toad that is caused by the activities of manufacturing industry sector follows this growth.The main objective of this research is to calculate the pollution rate caused by the activities of manufacturing industry sector and also manufacturing industry sector behavior in 1990 and 1995. So in turn it can be determined, which manufacturing industry sub sector needs to be noticed more By finding out the sub sector that contributes more to the pollution rate, the pollution rate can be decreased.Analysis applied is the Industrial Pollution Projection System (IPPS), which is developed by World Bank. The IPPS is combined with Macro Economics analysis and Input-Output model by considering the backward linkage index and forward linkage index of manufacturing industry sector.Based on calculation result, it can be concluded that there is a change on the most pollution contribution of the manufacturing industry sub sector from 1990 until 1995. The most pollute sectors for 1995 which pollutants of air are coded ISIC 3692, 3411, 3710, 3530 and 3540. The sectors, which pollutants of water are, coded ISIC 3710, 3411, 3720, 3511 and 3522. The sectors, which pollutants of soil are, coded ISIC 3511, 3710, 3720 and 3513. The sector, which contribute most in 1995 based on pollutant sorts are coded SO2 (3692), NO2 (3692) and Co (3710). The most pollute to the water called BOD are coded ISIC 3411, while toxic is coded 3511. In Indonesia, the manufacturing industry sector which has the high backward linkage contribute least to the pollution caused by the manufacturing industry sectors compared to the manufacturing industry sectors which have the high forward linkage.